Profiling of H3K27Ac Reveals the Influence of Asthma on the Epigenome of the Airway Epithelium - McErlean, Peter; Kelly, Audrey; Dhariwal, Jaideep; Kirtland, Max; Watson, Julie; Ranz, Ismael; Smith, Janet; Saxena, Alka; Cousins, David J.; Van Oosterhout, Antoon; Solari, Roberto; Edwards, Michael R.; et al. (Frontiers in Genetics, 2020)
Background: Asthma is a chronic airway disease driven by complex genetic-environmental interactions. The role of epigenetic modifications in bronchial epithelial cells (BECs) in asthma is poorly understood. Methods: We piloted genome-wide profiling of the enhancer-associated histone modification H3K27ac in BECs from people with asthma (n=4) and healthy controls (n=3). Results: We identified n=4,321 (FDR <0.05) regions exhibiting differential H3K27ac enrichment between asthma and health, clustering at genes associated predominately with epithelial processes (EMT). We identified initial evidence of asthma-associated Super-Enhancers encompassing genes encoding transcription factors (TP63) and enzymes regulating lipid metabolism (PTGS1). We integrated published datasets to identify epithelium-specific transcription factors associated with H3K27ac in asthma (TP73) and identify initial relationships between asthma-associated changes in H3K27ac and transcriptional profiles. Finally, we investigated the potential of CRISPR-based approaches to functionally evaluate H3K27ac-asthma landscape in vitro by identifying guide-RNAs capable of targeting acetylation to asthma DERs and inducing gene expression (TLR3). Conclusion: Our small pilot study validates genome-wide approaches for deciphering epigenetic mechanisms underlying asthma pathogenesis in the airways.